The Influence of Bank Ownership on Credit Supply: Evidence from the Recent Financial Crisis - Zuzana Fungáčová; Risto Herrala; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
This study examines how bank ownership influenced the credit supply during the recent financial crisis in Russia, where the banking sector consists of a mix of state-controlled banks, foreign-owned banks, and domestic private banks. To estimate credit supply changes, we employ an exhaustive dataset for Russian banks that covers the crisis period and apply an original approach based on stochastic frontier analysis. Our findings suggest bank ownership affected credit supply during the financial crisis and that the crisis led to an overall decrease in the credit supply. Relative to domestic private banks foreign-owned banks reduced their credit supply more and state-controlled banks less. This supports the hypothesis that foreign banks have a "lack of loyalty" to domestic actors during a crisis, as well as the view that an objective function of state-controlled banks leads them to support the economy during economic downturns.
URN:NBN:fi:bof-201408072081
Keywords: D14; G21; 330; bank; credit policy; foreign ownership; state ownership; stochastic frontier analysis